Frequency and phenotype of SPG11 and SPG15 in complicated hereditary spastic paraplegia - Schüle, R.; Schlipf, N.; Synofzik, M.; Klebe, S.; Klimpe, S.; Hehr, U.; Winner, Beate; Lindig, T.; Dotzer, A.; Rieß, O.; Winkler, Jürgen; Schöls, L.; et al. (Journal of Neurology Neurosurgery and Psychiatry, 2009)
Background: Hereditary spastic paraplegias (HSP) are clinically and genetically highly heterogeneous. Recently, two novel genes, SPG11 (spatacsin) and SPG15 (spastizin), associated with autosomal recessive HSP, were identified. Clinically, both are characterised by complicated HSP and a rather similar phenotype consisting of early onset spastic paraplegia, cognitive deficits, thin corpus callosum (TCC), peripheral neuropathy and mild cerebellar ataxia. Objective: To compare the frequency of SPG11 and SPG15 in patients with early onset complicated HSP and to further characterise the phenotype of SPG11 and SPG15. Results: A sample of 36 index patients with early onset complicated HSP and a family history compatible with autosomal recessive inheritance was collected and screened for mutations in SPG11 and SPG15. Overall frequency of SPG11 was 14% (5/36) but was considerably higher in patients with TCC (42%). One patient with mental retardation and thinning of the corpus callosum was compound heterozygous for two novel SPG15 mutations. Additionally, several new polymorphisms and sequence variants of unknown significance have been identified in the SPG15 gene. Conclusions: TCC seems to be the best phenotypic predictor for SPG11 as well as SPG15. No clinical features could discriminate between SPG11 and SPG15. Therefore, priority of genetic testing should be driven by mutation frequency that appears to be substantially higher in SPG11 than in SPG15.
CRIS-Team Scopus Importer:2024-08-07